Improvement of the photocatalytic hydrogen production activity of g-C3N4 by doping selenides as cocatalysts. (October 2018) - Yang, Dou-Dou; Sun, Xiao-Jun; Dong, Hong; Zhang, Xin; Tang, Hong-Liang; Sheng, Jing-Li; Wei, Jin-Zhi; Zhang, Feng-Ming
Abstract: Carbon nitride is emerging as leading candidate for photocatalyst which enables one to use light to drive hydrogen production reactions. However, noble-metal such as Pt was adopted to be effective co-catalyst to increase the activity of g-C3 N4 in most reactions which is costly. Herein, a novel g-C3 N4 -based photocatalyst with NiSe2 and CoSe2 as cocatalysts (abbreviated as CN-CoNiSe) in absence of noble-metal applied in photocatalytic hydrogen production was devised with a lamellar structure through a calcination process of the mixture of Ni 2+ doped ZIF-67 and g-C3 N4 for the first time in this work. The optimum photocatalytic activity in hydrogen evolution for CN-CoNiSe photocatalysts with a Ni 2+ doped ZIF-67 mass content in precursors of 5 wt% (854.1 μmol g −1 h −1 ) was up to 87.4 times as high as that of pure g-C3 N4 (9.77 μmol g −1 h −1 ). The greatly improved photocatalytic activity of CN-CoNiSe photocatalysts was mainly attributed to the synergistic effect of NiSe2, CoSe2 and g-C3 N4, which leads to enhanced charge transfer and separation rate based on the results of electrochemical experiments and photoluminescence. Graphical abstract: Here we present a light-driven novel g-C3 N4 -based photocatalysts with ZIF-67 derived cobalt and nickel selenides as cocatalysts for hydrogen production. fx1